Cost–consequence analysis of long-term prophylaxis in the treatment of von Willebrand disease in the Italian context - Schinco P; Cultrera D; Valeri F; Borchiellini A; Mantuano M; Gorla F; Savarese A; Teruzzi C (Dove Medical Press, 2014)
Piercarla Schinco,1 Dorina Cultrera,2 Federica Valeri,1 Alessandra Borchiellini,1 Michela Mantuano,3 Francesca Gorla,3 Alessia Savarese,3 Cristina Teruzzi3 1Hemostasis and Thrombosis Unit, Molinette Hospital of Turin, 2Department of Hematology, Hemophilia Regional Reference Center, University Hospital of Catania, 3HEMAR-Health Economics, Market Access and Reimbursement, Temas-A Quintiles Company, Milan, Italy Purpose: Prophylaxis with von Willebrand factor (VWF)/factor VIII (FVIII) concentrates is a potential approach for patients with severe von Willebrand disease (VWD). As far as we are aware, to date there have been no pharmacoeconomic analyses in order to assess the economic impact of treatments for severe VWD. The analysis presented here estimates the cost–benefit ratio of VWF with a low FVIII content when compared with VWF/FVIII concentrates currently used in Italy for long-term prophylaxis in patients with severe VWD. Methods: A cost–consequence analysis was undertaken to assess the economic impact of the treatment of severe VWD from the perspective both of the Italian National Health Service and society. The analysis was based on four case reports of long-term prophylaxis with VWD with VWF/FVIII concentrates and VWF with a low FVIII content. The costs per patient included direct and indirect costs for each treatment. Results: Considering the four case reports, health care costs (without cost of treatment) and indirect costs per patient per year were lower with VWF with a low FVIII content than VWF/FVIII concentrates. The total health care costs (without cost of treatment) and indirect costs avoided with VWF with a low FVIII content per patient per year ranged from €2,295 to €17,530 and from €1,867 to €4,978, respectively. Conclusion: VWF with a low FVIII content seems to be a cost-effective treatment option for patients with severe VWD. Although the drug cost per se is higher, the use of VWF with a low FVIII content is associated with decreased consumption of hospital resources and fewer lost working days due to bleedings and consequently with an improvement of the quality of life of the patients. Keywords: cost, VWF/FVIII concentrate, VWF with low FVIII content